THE EVELYN HUGO POLITENESS STRATEGY ANALYSIS IN TAYLOR JENKINS REID THE SEVEN HUSBANDS OF EVELYN HUGO - Yolanda Shelina Susanto; Bramantya Pradipta (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2024)
This research analysing about politeness strategy in the book entitled The Seven Husbands of Evelyn Hugo by Taylor Jenkins Reid. The analysis is based on the chosen utterances of the main character in the book, Evelyn Hugo as a speaker or when the other characters are being the speaker while having an interaction with her. This research used Brown & Levinson theory to analyse the data. The aims of this study are to analyse how many politeness strategies found and the mostly used politeness strategy in The Seven Husbands of Evelyn Hugo. The researcher used qualitative research and descriptive method in this study. The findings of this study found that positive politeness is the mostly used strategy. The book of The Seven Husbands of Evelyn Hugo is telling a story about Evelyn Hugo, one of the most legendary Hollywood actresses who requesting Monique Grant, an ordinary magazine writer to write a story about her whole life journey and experiences including her seven ex-husbands and the love of her life where both are surprisingly unexpected.